sj-docx-1-eso-10.1177_23969873221094705 – Supplemental material for One-year healthcare costs of patients with spontaneous intracerebral hemorrhage treated in the intensive care unit ... - Smeds, Marika; Skrifvars, Markus B; Reinikainen, Matti; Bendel, Stepani; Hoppu, Sanna; Laitio, Ruut; Ala-Kokko, Tero; Curtze, Sami; Sibolt, Gerli; Martinez-Majander, Nicolas; Raj, Rahul (SAGE Journals, 2022)
Supplemental material, sj-docx-1-eso-10.1177_23969873221094705 for One-year healthcare costs of patients with spontaneous intracerebral hemorrhage treated in the intensive care unit by Marika Smeds, Markus B Skrifvars, Matti Reinikainen, Stepani Bendel, Sanna Hoppu, Ruut Laitio, Tero Ala-Kokko, Sami Curtze, Gerli Sibolt, Nicolas Martinez-Majander and Rahul Raj in European Stroke Journal ...